X-RAY PROGRESSION AND ITS IMPACT ON THE FUNCTIONAL STATUS OF PATIENTS WITH EARLY RHEUMATOID ARTHRITIS DURING A 5-YEAR FOLLOW-UP - Yu. A. Ermakova; D. E. Karateev; E. L. Luchikhina; N. V. Demidova; A. V. Smirnov (Научно-практическая ревматология, 2015)
Objective: to assess progression of X-ray joint changes and their impact on functional status of patients with early rheumatoid arthritis (RA).Subjects and methods. The investigation enrolled 204 patients with early RA included in the RADICAL (Early Arthritis: Diagnosis, Outcomes, Criteria, Active Treatment) program in the period 2003 to 2007. The duration of the disease at the inclusion was less than 2 years. RA was diagnosed according to 1987 American College of Rheumatology (ACR) criteria. Rheumatoid factor was presentin 67.5% of the patients and anti-cyclic citrullinated peptide antibodies – in 57%. Women were 86.5%; median age was 49 [40; 58] years. The patients received traditional diseasemodifying antirheumatic drugs and biological agents (24%). Therapy response was monitored applying the tight control strategy. Main clinical and laboratory parameters, DAS28, and HAQ scores, and functional class and hand and foot X-ray were recorded every year.Results and discussion. After 5 years of follow-up, new erosions appeared in 57% of the patients. Joint erosions were present in 16.5% of the patients at the inclusion and in 73% following 5 years. At baseline, after 1, 2, 3, 4, and 5 years, the total erosion scores (modified Sharp score) was equal to 0 [0; 0], 0 [0; 1], 0 [0; 4], 1 [0; 8], 3 [0; 12], 6 [0; 14], respectively. A significant functional improvement could be achieved just during the first year of follow-up. Thus, the median HAQ value decreased from 1.125 [0.625; 1.75] to 0.5 [0.125; 1.0], reaching the population level. Following 2, 3, 4, and 5 years, the median HAQ was 0.5 [0; 1.0], 0.5 [0; 1.0], 0.5 [0; 1.0], and 0.75 [0.125; 1.125], respectively. There was a weak positive correlation between total erosion scores and HAQ in the eаrly stage of the disease. However, it became more marked after 3, 4, and 5 years (correlation coefficient, 0.38, 0.39, and 0.40,respectively; p < 0.01). Conclusion.In spite of the stable pattern of disease course, structural damage progression was seen in patients with early RA. However, detailed erosive component assessment using the modified Sharp score showed that the structural changes were modest in the majority of patients and HAQ value during the first 4 years of follow-up were comparable with the population level, which may be indicative of a rather favorable functional prognosis. Five years later, there was an increasing correlation between total erosion scores and HAQ. This may be responsible for higher HAQ scores after 5 years of follow-up